Evolution of superdislocation structures during tertiary creep of a nickel-based single-crystal superalloy at high temperature and low stress. (March 2017) - Tang, Yuling; Huang, Ming; Xiong, Jichun; Li, Jiarong; Zhu, Jing
Abstract: A second-generation nickel-based single crystal superalloys DD6 were creep tested in the [001] direction (within 15°) at 1100 °C/140 MPa. The specimen tested until rupture was investigated using scanning and transmission electron microscopy to determine the evolution of the dislocation behaviors during tertiary creep. It was found that the tertiary creep deformation was highly localized and inhomogeneous along the gauge length, and the types of superdislocations in γ′ rafts varied with the distances from the rupture surface, including individual screw dislocations, antiphase boundary-coupled dislocation pairs, and superlattice intrinsic stacking faults. It can be concluded that γ′ rafts shearing events occur in the following sequence with the evolution of tertiary creep: individual screw dislocations, antiphase boundary-coupled dislocation pairs, and superlattice intrinsic stacking faults. The origin of these transformations of superdislocation types and its influence on tertiary creep rate are discussed. It is proposed that at the microscopic level, a more reasonable explanation for the strain softening mechanism during the tertiary creep of nickel-based superalloys at high temperatures and low stresses is the emergence of new superdislocation types with higher mobility rather than the density rise of a single type of superdislocation produced during the later secondary creep stage. Graphical abstract: Image